Differences in the uptake and bioconcentration of dichlorodiphenyltrichloroethane by eight vegetable cultivars and their health risk assessments. (January 2019) - Wu, Xiaorong; Ding, Yongzhen; Wang, Ruigang; Rensing, Christopher; Li, Yuanping; Feng, Renwei
Abstract: Dichlorodiphenyltrichloroethane (DDT) is not easily degraded in soils, which will pose a threat to human health. We investigated the differences of eight vegetables' capacity to take up DDT, removing DDT from soil, and tolerating DDT (monitoring the responses of growth, root morphology and photosynthesis of vegetables to DDT). These vegetables included Chinese mustard (two genotypes, B.jf and B, jm), napa cabbage (two genotypes, B.coz and B.coc) and Bok choy (four genotypes, B.cz, B.cq, B.cs and B.chg). The results demonstrated that 5 mg kg −1 DDT did not display significant effects on the growth of most vegetables in this study. As compared to the control, 5 mg kg −1 DDT significantly increased the shoot and root biomass, the fine root numbers, and the fine root ratio for the genotype of B.chg. However, 5 mg kg −1 DDT exposure showed a negative effect on the shoot growth of two genotypes of napa cabbage. In general, 5 mg kg −1 DDT did not significantly affect the photosynthesis and root morphology of most vegetables in this study. Consuming these vegetables had a low non-cancer health risk, but showed a high cancer health risk. In addition, among the eight vegetables, B.chg accumulated less DDT in the edible parts and had low values of HRnon-cancer and HRcancer for consuming these vegetables containing DDT. Planting these vegetables might promote the degradation of DDT reducing its residual amount in soil. Graphical abstract: Highlights: Two genotypes of vegetables from Napa cabbage were sensitive to DTT. Four genotypes of vegetables from Bok choy had relatively high tolerances to DDT. Photosynthesis and root morphology of most vegetables were not obviously affected. Long-term intake of the vegetables by humans has a high carcinogenic risk. Planting vegetables can promote the removal efficiency of DDT from soils.